Developing observational measures of performance in surgical teams. - Healey, A; Undre, S; Vincent, C (2004)
Team performance is increasingly recognised as an essential foundation of good surgical care and a determinant of good surgical outcome. To understand team performance and to develop team training, reliable and valid measures of team performance are necessary. Currently there is no firm consensus on how to measure teamwork, partly because of a lack of empirical data to validate measures. The input-process-output model provides a framework for surgical team studies. Objective observational measures are needed in surgery as a basis for interdisciplinary team assessment and training. The "observational teamwork assessment for surgery" (OTAS) tool assesses two facets of the surgical process. Observer 1 monitors specific tasks carried out by team members, under the categories patient, environment, equipment, provisions, and communications. Observer 2 uses a behavioural observation scale to rate behaviour for the three surgical phases (pre-operative, operative, and post-operative) with components of teamwork: cooperation, leadership, coordination, awareness, and communication. Illustrative data from an initial series of 50 cases is presented here. The OTAS tool enables two independent observers, a surgeon and psychologist, to record detailed information both on what the theatre team does and how they do it, and has the potential to identify constraints on performance that might relate to surgical outcome.